Broadband emission of single-phase Ca3Sc2Si3O12:Cr3+/Ln3+ (Ln = Nd, Yb, Ce) phosphors for novel solid-state light sources with visible to near-infrared light output. Issue 11 (1st August 2019) - Yao, Leqi; Shao, Qiyue; Xu, Xiaoxue; Dong, Yan; Liang, Chao; He, Jinhua; Jiang, Jianqing
Abstract: Novel single-component phosphors Ca3 Sc2 Si3 O12 :Cr 3+ /Ln 3+ (CSS:Cr 3+ /Ln 3+, Ln = Nd, Yb, Ce) with broadband near-infrared (NIR) emissions are synthesized. Their phase structure, photoluminescence properties and energy transfer between Cr 3+ and Ln 3+ ions are investigated. In the CSS host, Cr 3+ ions occupy Sc 3+ sites with low-field octahedral coordination, and thus show a broadband emission in 700–900 nm under the blue light excitation. Nd 3+, Yb 3+ and Ce 3+ ions substitute Ca 2+ sites in CSS, where Nd 3+ and Yb 3+ ions emit the NIR light in 900–1100 nm and their excitation efficiencies at ∼450 nm are greatly enhanced by utilizing the energy transfer from Cr 3+ to Nd 3+ /Yb 3+ ions. Ce 3+ ions can further enhance the absorption of CSS:Cr 3+ /Ln 3+ phosphors to the blue light, and at the same time contribute to the visible emission in 480–650 nm. Furthermore, CSS:Cr 3+ /Ln 3+ phosphors show good thermal stability, and approximately 79% of the initial emission intensity is sustained at 150 °C. A phosphor-converted LED (pc-LED) prototype is fabricated by integrating the as-prepared phosphor CSS:Cr 3+ /Ln 3+ and the commercial phosphor CaAlSiN3 :Eu 2+ with the blue LED chip, showing a super broadband emission ranging from 450 to 1100 nm. This finding shows the potential application of CSS:Cr 3+ /Ln 3+ phosphors in broadband NIR pc-LEDs or super broadband LED sources with visible to NIR light output.